2001
DOI: 10.1148/radiographics.21.2.g01mr10507
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Fluoroscopic Imaging System Contrast by Using Video Waveform Monitoring

Abstract: A noninvasive method was developed for quantifying the overall contrast of fluoroscopic imaging systems within the clinical setting by using a simple phantom and common video test equipment. In this method, an acrylic phantom with four holes filled with varying amounts of air and aluminum is placed on the entrance exposure side of a patient-equivalent acrylic phantom. The air-and aluminum-filled holes provide a stepped gray-scale pattern that is displayed on the examination room viewing monitor when the phanto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Despite the possibility to further reduce the radiation exposure, concern remains regarding the adequacy of image quality, especially of central images on the torso; however, it is reported that most radiologists start to detect contrast changes in radiographic images only when such changes result in approximately 15% change of the image contrast index. 6 Hence it is possible to reduce the radiation exposure by manipulating the dose parameters without appreciable changes in image quality. In addition, as most haemodialysis accesses are peripheral, there may be more scope to manipulate the radiation dose than imaging of central torso imaging such as coronary artery imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the possibility to further reduce the radiation exposure, concern remains regarding the adequacy of image quality, especially of central images on the torso; however, it is reported that most radiologists start to detect contrast changes in radiographic images only when such changes result in approximately 15% change of the image contrast index. 6 Hence it is possible to reduce the radiation exposure by manipulating the dose parameters without appreciable changes in image quality. In addition, as most haemodialysis accesses are peripheral, there may be more scope to manipulate the radiation dose than imaging of central torso imaging such as coronary artery imaging.…”
Section: Introductionmentioning
confidence: 99%